The shift in the role of teachers in the learning process. - Vighnarajah, .; Luan, Wong Su; Abu Bakar, Kamariah (EuroJournals, 2008)
Numerous studies have established that active participation in the learning process is more effective in a learning environment that emulates a real-world learning environment. In a traditional teaching and learning environment, only little learning is taking place in the classroom even though there appears to be an active shift of information. Studies have also clearly established that the role of the teacher alone is able to crush or nurture a student’s participation in the learning process. Hence, it is necessary to bring about a two-way transfer of knowledge between students and teachers as it requires optimum students’ participation. This paper brings into discussion the shift in the role of teachers in the learning process, from the traditional teaching and learning environment to a learning environment that encourages active students’ participation in the learning process. Respectively, this paper puts emphasis on the important role a teacher shoulders in shifting students from a passive role to an active role in a teaching and learning process. These characteristics of an effective teacher are grounded in the constructivism theory of learning, prior to which a brief description of the behaviorism and cognitivism theories is provided.